Cryptocurrency price prediction using Social Media Data Mining and Epidemic Modeling - Safa, Bushra; Eva, Sanjida Noushin; Hossain, Sania; Salauddin, A.K.M; Upoma, Lubaba Fakruddin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.